Efeito da exposição à atrazina nas brânquias de Poecilia vivipara aclimatados a diferentes salinidades - Azevedo, Vinicius Cavicchioli (Universidade Federal de São Carlos, 2013)
Atrazine is an herbicide widely used in agriculture, cause morphological and biochemical changes in organs of many species. The estuarine environments are highly dynamic under constant variations of physicochemical water. Currently there are no proposals to regulate the discharge of pollutants in environments that consider the interactions between contaminants, the physicochemical properties and biota. As also few studies, evaluating biomarkers in animals exposed to contamination with simultaneously physicochemical variations. Therefore, this study aimed to evaluate the effects of atrazine on ionic regulation evaluating the activity of the enzyme Na+/K+ ATPase (NKA) , V-H+ - ATPase (V-AH) and carbonic anhydrase (CA), changes in the morphology of cells rich in mitochondria (MRC) and mucous cells (MC), the antioxidant system evaluating the total antioxidant capacity against peroxyl radicals (ACAP), glutathione-s-transferase (GST), level of lipid peroxidation (LPO) and histopathological changes in Poecilia vivipara acclimated to different salinities. Individuals of P. vivipara were acclimated in salinity 25, 16, 8 and fresh water and subsequently exposed to three different concentrations of atrazine (2, 10 and 100 mg L- 1). The NKA increased with decreasing salinity and showed different responses against atrazine depending of acclimatization salinity the animals. The activity of V - HA increased front of the reduce of salinity, exposure to atrazine increased the activity of V-HA in all the different acclimatization, and CA activity was inhibited with decreasing salinity and exposure to atrazine. The density and fractional area of MRC increased with the decrease in the salinity and atrazine exposure decreased these two parameters in all salinities. The density and fractional area of CMs decreased with salinity and atrazine exposure caused an increase in density and fractional area of CMs, suggesting an increased production and release of mucus in an attempt to prevent oxidative damage. The ACAP and GST activity in gills of P. viviparous after exposure to atrazine showed different responses for each salinity acclimatization. The results show that in all salinity acclimatization atrazine causes changes in gill tissue, which may compromise its function.
Keywords: Fisiologia; Osmorregulação; Estresse oxidativo; Histopatologia; CIENCIAS BIOLOGICAS::FISIOLOGIA